Urethral Orifice Genital Herpes Caused by HSV-1 in a Female Patient: A Case Report - Jia-Yi Yang; Xiao-Hui Mo; Xiu-Li Wang (Wolters Kluwer Health, 2021)
Abstract. Introduction:. Genital herpes is one of the most common sexually transmitted infections worldwide. Most genital herpes occur on the genitalia, perineum, buttocks, upper thighs, or perianal areas. However, there were reports of rare cases of genital herpes on urethral orifice. Herein, we report a case of a patient who was diagnosed with urethral orifice genital herpes, a place likely to be ignored. Case presentation:. A 53-year-old woman presented with vagina pruritus at first, with subsequent burning sensation around urethra. Mycostatin and mycospor were administered for the treatment of the pruritus. Then levofloxacin was prescribed. Finally, the patient was given treatment with acyclovir. Different from other cases, the investigation showed herpes simplex virus type 1 DNA positive and herpes simplex virus type 2 DNA negative by PCR. The patient was therefore diagnosed with genital herpes. Discussion:. Most genital herpes happen on the genitalia, perineum, buttocks, upper thighs, or perianal areas. Few cases have been reported that genital herpes occurred on urethral orifice till now. Conclusion:. If there is no typical symptoms that patient present with herpes simplex virus type 1 or 2 positive, urethral orifice genital herpes should be considered.